CYSTICERCOSIS OF BREAST PRESENTING AS FIBROADENOMA - Agarwal, Anshoo; Osman, Muhamed T (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Breast lump is a common diagnostic problem both to the general practitioner and to the surgeons. However, rare breast lesions are often misdiagnosed clinically with other diagnoses. We present a case of cysticercosis of breast in a 23-year-old woman presented with a 3-month history of right breast lump. Clinical examination revealed a mobile, painless, 2.0 cm mass in the right breast similar to fibroadenoma. The axilla and nipples had no abnormalities. The patient underwent resection of the mass, and a cystic lesion was found. Microscopic examination revealed a cystic cavity containing larvae and it consistent with cysticerci. Characteristic features of this uncommon location are discussed based on a review of the literature. This case report emphasizes the fact that although the breast is unusual site for cysticercosis, it should be considered as differential diagnosis while dealing with a painless, freely mobile lump in the breast, especially in the endemic area. Keywords: Breast, Cysticercosis, Histopathology.